Detecting latent DNA in wildlife forensic science investigations. Issue 4 (July 2020) - Kanokwongnuwut, Piyamas; Kirkbride, K. Paul; Linacre, Adrian
Highlights: Wildlife crime may occur in remote environments with many days gap before any sampling. 5 people touched six substrates which were then placed outside for up to 28 days. A decline in cell number was recorded from items sampled at 7, 14 and 28 days. Cells could be visualised after exposure to the environment for 28 days. Full DNA profiles were generated from samples even after 28 days exposure.